2009
DOI: 10.1002/ajp.20710
|View full text |Cite
|
Sign up to set email alerts
|

Macaque–human interactions and the societal perceptions of macaques in Singapore

Abstract: Humans and long-tailed macaques (Macaca fascicularis) interface in several locations in Singapore. We investigated six of these interface zones to assess the level of conflict between the two species. We observed macaque-to-human interactions and distributed questionnaires to residents and visitors of nature reserves. We observed an average of two macaque-to-human interactions per hour at the sites, which included affiliative or submissive behaviors (46.9%), aggression (19.1%), taking food and other items (18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
71
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 158 publications
(80 citation statements)
references
References 24 publications
4
71
1
2
Order By: Relevance
“…These observations are similar to those made by Fuentes (2006) when he observed differences between types of people and the interactions between humans and macaques at Bali and Gibraltar. In addition, work in Singapore has shown that residents and visitors to nature parks with macaques have very different attitudes and very different experiences with macaques (Sha et al, 2009b). Studying the behavioral flexibility and adaptability of wild and human-altered habitats of Assamese macaques (M. assamensis) in the in central Nepal also showed that provisioning alters the activity and feeding behavior of macaques.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations are similar to those made by Fuentes (2006) when he observed differences between types of people and the interactions between humans and macaques at Bali and Gibraltar. In addition, work in Singapore has shown that residents and visitors to nature parks with macaques have very different attitudes and very different experiences with macaques (Sha et al, 2009b). Studying the behavioral flexibility and adaptability of wild and human-altered habitats of Assamese macaques (M. assamensis) in the in central Nepal also showed that provisioning alters the activity and feeding behavior of macaques.…”
Section: Discussionmentioning
confidence: 99%
“…They also occasionally threaten or cause harm to humans by acting aggressively. Aggressive macaque-to-human behavior is mainly the result of direct competition over contestable food sources (Fuentes, 2006;Fuentes et al, 2008;Sha et al, 2009b), but can also occur due to human prompting (i.e., teasing, chasing, approaching to close, etc. ), defense of young and interference with mating activity ((McCarthy et al, 2009;Gumert et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for cross-species transmission exists wherever humans and NHP come into contact. Human-NHP interaction is common in Asia, particularly in Bangladesh, where humans and NHP have lived sympatrically for centuries (6)(7)(8)(9). The contexts of contact between humans and NHP in Bangladesh are a microcosm of what is seen in much of South and Southeast Asia.…”
mentioning
confidence: 99%
“…Local residents, however, should take pride in Gibraltar; they should deal with their litter appropriately and consider the needs of those who will be disproportionately affected by macaques, encouraged by readily available extra food, spreading into urban areas. A study from Singapore revealed that residents reported more problems with long-tailed macaques than tourists did, but held overall neutral views of the macaques, despite experiencing occasional raids by macaques on their properties [Sha et al, 2009]. Several researchers have shown that adult male macaques are more likely than females or juveniles to engage with tourists, especially in aggressive encounters [Fuentes and Gamerl, 2005;Fuentes, 2006;Hsu et al, 2008]; this is reflected in complaints about adult male Barbary macaques in the "Monkey Sightings" group, demonstrating the impact felt by residents when tourism inures primates to a range of human interaction.…”
Section: Tourismmentioning
confidence: 99%